Comparative Stratigraphic and Geochronological Evolution of the Northern Damara Supergroup in Namibia and the Katanga Supergroup in the Lufilian Arc of Central Africa - Miller, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2013)
SUMMARY The Damara Supergroup in Namibia and the Katanga Supergroup in the Central African Copperbelt (some 1000 km apart) are characterized by rock successions indicative of almost coeval orogenic evolution through phases of intracontinental rifting, spreading, continental rupture, subduction, ocean closure and continental collision in what appears to have been a single, elongate orogenic belt. Rifting began at about 880 Ma and lasted until about 800 or 756 Ma. Post-rift thermal sag and marine transgression produced the first correlatable stratigraphic units, the argillaceous Beesvlakte and Ore Shale Formations, in northern, carbonate-dominated platformal successions on the Damaran Northern Platform and the Katangan Lufilian Arc or Fold Belt, respectively. Sturtian (~735 Ma) and Marinoan (635 Ma) glacial units are common to both successions as well as syntectonic molasse sequences (~595–550 Ma). Continental collision occurred at about 542 Ma and the post-tectonic peak of regional meta-morphism was at about 535–530 Ma. Mineral ages record cooling to about 460 Ma. The extensive occurrence of stratabound, but not stratiform, copper mineralization, evaporitic minerals, salt and thrust tectonics, syntectonic breccias, and intense alteration in the Lufilian Arc have no significant equivalents in the Northern Platform. However, the Beesvlakte Formation has both concordant and strongly discordant styles of copper mineralization and the mode of occurrence of mineralization in the Copperbelt can be a guide to exploration in Namibia.